A survey of retractions in the cardiovascular literature. (15th February 2022) - Audisio, Katia; Robinson, N. Bryce; Soletti, Giovanni J.; Cancelli, Gianmarco; Dimagli, Arnaldo; Spadaccio, Cristiano; Olaria, Roberto Perezgrovas; Chadow, David; Rahouma, Mohamed; Demetres, Michelle; Tam, Derrick Y.; Benedetto, Umberto; et al.
Abstract: Background: Retractions of erroneous and fraudulent papers from the biomedical literature continue to be a major concern. The aim of this analysis is to summarize trends of retractions in the cardiovascular literature over the past four decades. Methods: A review of the Retraction Watch database for retracted articles published between 1978 and 2020 in the cardiovascular literature was performed. Retractions with the term "medicine" in the subject code were selected. Titles and abstracts were reviewed and only retractions of articles in cardiovascular medicine and surgery were included. Results: 459 retraction notices published in 228 journals were identified. The number of retractions increased with time from 1 in 1991 to 48 at the end of 2019 (P < 0.001). Overall, the yearly percentage of retraction increased during the study period (P < 0.001) but decreased after 2015. China had the highest percentage of retractions when compared to other countries (P < 0.001). The majority of articles were retracted for scientific misconduct (n = 289, 63.0%); retractions due to scientific misconduct increased significantly over the study period (P = 0.04) but decreased after 2015. The median time from publication to retraction was 1.4 years (interquartile range [IQR]: 0.6–3.8) and decreased significantly over time (P < 0.001). The median number of citations of retracted articles was 8.0. Conclusions: The number of retractions and the yearly percentage of retraction in the cardiovascular literature increased significantly during the study period, although a decrease was seen after 2015. Scientific misconduct represents the most common reason for retraction, although a reduction has been observed in the last five years. Graphical abstract: Unlabelled Image Highlights: Retractions in the cardiovascular field have increased annually from 1978 to 2015. China, USA, and Japan have the highest absolute number of retractions. Two authors are responsible for 7.2% of the retractions alone. Scientific misconduct represents the most common reason for retraction. Most retractions are from journals with an impact factor lower than 5.